Dark sides, Tyranny, and Dragons - Thomas Ryberg (Journal of Problem Based Learning in Higher Education, 2024)
This article introduces work originating from the area of Networked Learning that seeks to problematise and critically discuss notions such as ‘collaboration’, ‘community’, and ‘participation’. It argues that there is a dark and shadowy side to these ideals, which we need to attend to in a reflexive manner. To this end, it introduces ideas of heteropian spaces and emphasizes the value of working with difference, and consent over consensus.